PTPRM methylation induced by FN1 promotes the development of glioblastoma by activating STAT3 signalling - Jian Song; Di Zhao; Guozhu Sun; Jiankai Yang; Zhongqiang Lv; Baohua Jiao (Taylor & Francis Group, 2021)
Context The phosphorylation of signal transducer and activator of transcription protein 3 (STAT3) is up-regulated in glioblastoma (GBM) cells and is regulated by protein tyrosine phosphatase receptor type M (PTPRM). Fibronectin-1 (FN1) is also reported to be up-regulated in GBM. Objective We explored the role of FN1-induced PTPRM methylation in GBM. Materials and methods The lentivirus particles of oe-PTPRM, sh-PTPRM, oe-FN1, sh-FN1, or their negative controls (NSCs) were transfected into GBM cells with or without stattic (0.5 μM, 24 h) or 5-aza (1 μM, 0, 2, 4 h) treatments. Methylation-specific PCR was performed to detect PTPRM methylation levels. Results PTPRM was down-regulated (0.373 ± 0.124- and 0.455 ± 0.109-fold), FN1 and p-STAT3 were up-regulated (p < 0.001) in A172 and U87 MG cells as compared to NSCs. Overexpressing PTPRM inhibited STAT3 phosphorylation. Interfering with PTPRM increased colony numbers in A172 and U-87 MG cells (2.253 ± 0.111- and 2.043 ± 0.19-fold), and stattic reduced them. Cell viability was reduced after treatment with 5-aza in A172 and U-87 MG cells (p < 0.05). P-STAT3 was down-regulated after 5-aza treatment. Overexpressing FN1 decreased PTPRM levels (p < 0.001), knockdown of FN1 decreased PTPRM methylation and inhibited STAT3 phosphorylation. Overexpressing FN1 increased cell viability (1.497 ± 0.114- and 1.460 ± 0.151-fold), and stattic or 5-aza reversed such effects (p < 0.05). Discussion and conclusions The up-regulation of FN1 reduced PTPRM by increasing its methylation, resulting in an increase of STAT3 phosphorylation and promoting GBM cell proliferation. Interfering with FN1 may be a potential therapeutic target for GBM.